The Fort of San Cristóbal (Ansoáin, Navarra): an approach from public archeology and the emotion and sentiment analysis - Vélaz Ciaurriz, David (Huarte de San Juan. Geografía e Historia, 2024)
Public Archeology understands that the research of any cultural asset only is completed if the understanding guidelines that underlie in the relationship with the recipients of these assets are taken into account. In this sense, this work aims to analyse the feelings and emotions that the Fuerte de San Cristóbal awakens in society, understanding that it is valuable information to take into account in the process of interpreting this historical site. A methodological proposal is presented from an R programming environment that allows extrapolating feelings and emotions that underlie texts – in this case Google reviews. However, the work proposal may be applied to different data samples related to other cultural assets. From the point of view of feelings, a moderate negative polarity and a predominance of emotions of fear and sadness are identified.
Keywords: History; Archaeology; sentiments; emotions; shyuzet